The Republic of Moldova : Staff Report for the 2015 Article IV Consultation and Third Post-Program Monitoring Discussions-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Moldova. (IMF Staff Country Reports; Country Report ;, 2016)
This 2015 Article IV Consultation highlights that Moldova's economic growth, at 3.6 percent, came in surprisingly strong in the first half of 2015 and was largely driven by net exports. Reserves fell by about a third between October 2014 and February 2015, but have been stable since. Net outflows in the financial account surged at end-2014, owing to election uncertainty and the banking crisis, but the outflow in currency and deposits tapered off in the second quarter of 2015. The near-term outlook is difficult. The economy is projected to contract by 1.75 percent in 2015, followed by a marginal recovery of about 1.5 percent in 2016. Deep reform is needed in the financial sector.